Amplitude of spectral area of ventricular fibrillation as a guide for low energy defibrillation level in patients with out-of-hospital cardiac arrest. (3rd May 2023) - Gentile, F R; Fasolino, A; Wik, L; Aramendi, E; Isasi, I; Steen-Hansen, J E; Baldi, E; Compagnoni, S; Quilico, F; Contri, E; Palo, A; Primi, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The optimal energy level for shock in biphasic waveform defibrillation represents a significant knowledge gap. Different energy regimens have been trialed; however, a selection criterion which may help in adopting one approach over another has never been identified. Choosing the maximum energy may be an option but current-induced myocardial damage should not be neglected and an effort to tailor energy delivery is desirable. Purpose: To assess whether amplitude spectral area (AMSA) of VF can guide the dose-regimens of defibrillation in out-of-hospital cardiac arrest (OHCA) patients. Methods: This is a multicenter study based on the data from some of the largest OHCA registers in Europe, which enrolled 830 OHCA patients who received at least one shock during advanced resuscitation. AMSA values were calculated by retrospectively analyzing the data collected by the Corpuls 3 and LIFEPAK 12/15 monitors/defibrillators and by using a 2-second-pre-shock ECG interval. Results: Among 830 OHCAs, 2135 shocks were delivered from a minimum energy level of 150 J to a maximum of 360 J. The AMSA values of efficacious shocks delivered at 150 J were higher compared to those of efficacious shock at 360 J [13.1 (IQR 10.2-17.1) vs 11.8 (IQR 8.3-15.2) HzxmV; p<0.01). In a multivariate analysis corrected for time to each shock, sex, age, amiodarone administration and study center, AMSA values, and not the dose of the shock energy, was significantly associated with the probability of shock success [OR 5.8, (95%CI 4.7-7.3); p< 0.01]. By dividing the total shocks into three tertiles based on AMSA values (T1: 0.8-6.9 Hz×mV; T2: 6.9-11.8 Hz×mV; T3: 11.8-63.2 Hz×mV), the rate of shock success at low energy was significantly higher in the tertile with highest AMSA values (T3: 38% vs T2: 15% vs T1: 5%; p<0.01). Particularly in T3, low energy was more effective than high energy shocks (38% vs 23%, p < 0.001). Conclusion: This is the first study to identify a datapoint to guide decision-making with regards to defibrillation with lower energy levels. AMSA could indeed guide the selection of energy levels in order to optimize efficaciousness in restoring a perfusing rhythm while minimizing the contribution to myocardial dysfunction.